Surgical Approaches for Prevention of Neuroma at Time of Peripheral Nerve Injury - Scott, Benjamin B.; Winograd, Jonathan M.; Redmond, Robert W. (Frontiers in Surgery, 2022)
Painful neuroma is a frequent sequela of peripheral nerve injury which can result in pain and decreased quality of life for the patient, often necessitating surgical intervention. End neuromas are benign neural tumors that commonly form after nerve transection, when axons from the proximal nerve stump regenerate in a disorganized manner in an attempt to recreate nerve continuity. Inflammation and collagen remodeling leads to a bulbous end neuroma which can become symptomatic and result in decreased quality of life. This review covers surgical prophylaxis of end neuroma formation at time of injury, rather than treatment of existing neuroma and prevention of recurrence. The current accepted methods to prevent end neuroma formation at time of injury include different mechanisms to inhibit the regenerative response or provide a conduit for organized regrowth, with mixed results. Approaches include proximal nerve stump capping, nerve implantation into bone, muscle and vein, various pharmacologic methods to inhibit axonal growth, and mechanisms to guide axonal growth after injury. This article reviews historical treatments that aimed to prevent end neuroma formation as well as current and experimental treatments, and seeks to provide a concise, comprehensive resource for current and future therapies aimed at preventing neuroma formation.